A Non-enzymatic Electrochemical Sensor for Glucose Detection Based on Ag@TiO2@ Metal-Organic Framework (ZIF-67) Nanocomposite - Arif, Dooa; Hussain, Zakir; Sohail, Manzar; Liaqat, Muhammad Arman; Khan, Muzamil Ahmad; Noor, Tayyaba (Frontiers in Chemistry, 2020)
This work presents the preparation of an efficient and sensitive glucose sensor for the detection of glucose in an alkaline media. The glucose sensor is composed of a metal organic framework (MOF) composite comprising Ag@TiO2 nanoparticles. The hybrid of Ag@TiO2 encapsulated in ZIF-67 was synthesized by the solvothermal method and applied onto a glassy carbon electrode (GCE) for the non-enzymatic sensing of glucose. The porosity of ZIF-67 was favorable for the unhindered diffusion and entrapment of glucose and its cavities served as reaction vessels. The electrochemical behavior of Ag@TiO2@ZIF-67 showed amplified results when compared with that of Ag@TiO2 and ZIF-67. Cyclic tests toward the oxidation of glucose has demonstrated excellent stability of a MOF-based hybrid sensor. The sensor based on Ag@TiO2@ZIF-67 showed high sensitivity of 0.788 μAμM−1cm−2 with a linear concentration range of 48 μM−1 mM and a response time of 5 s with an excellent detection limit of 0.99 μM (S/N = 3).